Tecnologias, mídias, criação e hipertextualidade na transformação da informação em conhecimento interativo - Jorente, Maria José Vicentini [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The object of study of this research is defined in terms of cognitive and emotional changes in the process of acquiring knowledge, supported by new technologies of information and communication (ICTs): how these changes transform the old paradigms of Information Science. The hypothesis is that the generation of products of contemporary creation is influenced and facilitated by new forms of perception and sensitivity offered by postvanguard media. The thesis is that procedures used to prepare professional designers in imagery can be extended, as far as the media invade the cognitive process of knowledge nowadays, determining means of perception, procedures and facilitating access to information as a whole. The technology interfaces interfere in shaping information and its perception, dissemination and reproduction in hypertextual and intersemiotical’s systematic interactions. The proposed update of the concepts and procedures is based on the actualization of the concepts of science and contemporary art treated in accordance with new paradigms of Information Science. In these, science and aesthetics go together in order to create environments of communication conveyed by self-organization and new habits of selfarchiving. They are controlled by peers and mentors in daily pages, terms of annotation of electronic communication, leading to empowerment through collaborative practice. The thesis articulates a theoretical universe with application in laboratory practices. The theoretical basis is defined within the environment of the object of study -the information conveyed by the media as a post-vanguard dynamic chaotic subsystem permeated by other subsystems- such as semiotics, especially intersemiotics translations and hybridizations modeled by the media in post-vanguard. Concepts of remix and reproducibility are treated subsequently to the intersemiosis. It is also sought to identify... (Complete abstract click electronic access below)

O objeto de estudo desta pesquisa está definido no plano das mudanças cognitivas e emocionais, no processo de aquisição de conhecimento patrocinado pelas novas tecnologias e em como estas mudanças transformam os antigos paradigmas da Ciência da Informação. A hipótese levantada é de que a genética dos produtos de criação contemporânea seja influenciada e facilitada por novas formas de sensibilidade e percepção da informação proporcionadas pelas mídias pós-vanguardistas. A tese é que procedimentos usados para preparar criadores, ensinando as codificações imagéticas, possam ser estendidos pois as mídias invadem o processo cognitivo gerativo do conhecimento, determinam formas de percepção, metodologias e facilitam o acesso às informações como um todo atualmente. As interfaces tecnológicas interferem na conformação da informação e na sua percepção, disseminação, reprodução e interação sistemática hipertextualmente e intersemioticamente. A proposta de atualização dos procedimentos tem por base a atualização dos conceitos de ciência e arte contemporâneos tratados de acordo com os novos paradigmas da Ciência da Informação. Nestes, ciência e estética caminham juntas para criar ambientes de comunicação por auto-organização e por novos hábitos de auto-arquivamento controlados por pares e mentores em páginas-diários, cadernos de anotação de comunicação eletrônica levando a empoderamento via usos colaborativos. A tese articula um universo teórico com aplicação em práticas laboratoriais. No embasamento teórico se define a ambiência do objeto de estudo, as informações veiculadas pelas mídias pós-vanguardistas como um subsistema dinâmico caótico permeado por outros subsistemas, como o da semiótica, especialmente das traduções intersemióticas, modelizadas nas hibridizações das mídias pós-vanguardistas...
Keywords: Ciência da informação; Sistemas de hipertexto; Conhecimento interativo; Hipertextualidade; Novas tecnologias de informação; Information Science; New Technologies of information; Intersemiotics translations